2014
DOI: 10.1002/ijc.28734
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of a putative tumor suppressor BMP4 by SOX2 promotes growth of lung squamous cell carcinoma

Abstract: SOX2 is a transcription factor essential for self-renewal and pluripotency of embryonic stem cells. Recently, SOX2 was found overexpressed in the majority of the lung squamous cell carcinoma (SQC), in which it acts as a lineage-survival oncogene. However, downstream targets/pathways of SOX2 in lung SQC cells remain to be identified. Here, we show that BMP4 is a downstream target of SOX2 in lung SQC. We found that SOX2-silencing-mediated inhibition of cell growth was accompanied by upregulation of BMP4 mRNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 28 publications
2
32
0
1
Order By: Relevance
“…E) ( p < .01). In accordance with the negative correlation between SOX2 and BMP4 in lung squamous cell carcinoma cells , knockdown of the SOX2 increased BMP4 transcription in MM‐MSCs (Fig. F, 7G) ( p < .01).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…E) ( p < .01). In accordance with the negative correlation between SOX2 and BMP4 in lung squamous cell carcinoma cells , knockdown of the SOX2 increased BMP4 transcription in MM‐MSCs (Fig. F, 7G) ( p < .01).…”
Section: Resultssupporting
confidence: 76%
“…Previous studies revealed that SOX2 could negatively regulate BMP4 promoter activity through binding to the promoter . To elucidate the role of SOX2 in the osteogenic differentiation of MSCs, we determined SOX2 expression during the osteogenic differentiation of MSCs by qPCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased expression of SOX2 has been proposed to maintain some characteristics of cancer cells [33,34]. Knocking-down or downregulation of SOX2 inhibits cancer cell growth and metastatic potential [35][36][37]. The expression of SOX2 is critical to maintain the selfrenewal in embryonic stem cells and neural progenitor cells [38][39][40].…”
Section: The Potential Targetsmentioning
confidence: 99%
“…Öte yandan, akciğerin skuamöz hücreli karsinomunda, Sox2'nin BMP4 promotoruna bağlaranak onu negatif şekilde düzenlediği ve Sox2 inhibisyonunun, BMP4 protein ifadesini arttırarak, hücre proliferasyonunu arttırdığı gösterilmiştir (62).…”
Section: Sox2'nin Akciğer Kanseri Gelişimindeki Rolüunclassified